TRAINING ON THE USE OF THE CASHIER APPLICATION AND CREATION OF A COMPANY PROFILE WEBSITE TO INCREASE RM'S INCOME. INTAN SARI MEDAN - Inneke Qamariah; Malinda Sari Sembiring; Fauziah Kumalasari; Dio Agung Herubawa (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2023)
There are many Padang restaurants in Medan city with a variety of advantages. Intense competition of course means that partners must be ready to carry out the best strategic management they can, both in the areas of food production, financial management, service, and realizing the importance of promotions for increasing income. RM location. Intan Sari is very strategic as a place of business. This can be seen from the area which is busy with people and along the road there are many eating places offering various types of food. This of course creates business competition between traders there. So a better marketing strategy is needed to support increased income. Based on the results of interviews and observations conducted, several obstacles were found that resulted in partners not being able to compete with similar businesses, such as financial management that was not yet transparent and accountable, marketing techniques that were still conventional, sales volumes that were not optimal and facilities and infrastructure/facilities that were inadequate. Through this program, the implementing team offers several solutions in the form of training and assistance in using the cashier application, providing digital-based marketing assistance and training by creating company profile websites and official partner social media accounts, providing equipment assistance to increase sales volume and providing facility assistance (desk sets and seats) to improve excellent service. So that in the end there will be an increase in income at R.M intan Sari Medan.